Protoide. šaknis *leh3u- „lietis, tekėti…“ baltų kalbose (liet. liūtìs ir lietùs) - Karaliūnas, Simas (Baltistica, 1992)
THE PROTOIDE. ROOT *leh3u- “flow, stream, pour…” IN BALTIC (LITH. liūtìs “heavy shower, downpour” AND lietùs “rain”) The relationship of Lith. liū́tis/liūtìs “heavy shower, downpour” and lietùs “rain”, as has been suggested by P. Skardžius, may be understood only in the Protoindoeuropean prospect. Hit. lahui “it flows, streams, pours…”, Gr. λoύει “he bathes, washes” and Lat. lavit “id.” seem to have the apophonic o and their protoform should be reconstructed as *leh3-e/o, as proposed by F. Bader. Its root vocalism e is attested in Mycenaean Gr. re-wo-te-re-jo and Lith. liaũkti (-ia) “flow, stream” <* leu(k)-. Lith. liū́tis/liūtìs with suffix -ti- rests on the allomorph *lh3u- of this protoIE. root, attested, for instance, in Hit. li-lhuu̯ai- , le-lhuu̯ai- and possibly in Lat. perfect lāvī, if from *lh3u-ai. A verbal form * (a)pa-lh3u- [cf. Lat. ab-luō, Gr. άπο-λούω, Hit. appa(n) lahhu-] might have served as a basis for derivatives Lith. pa-liū́tis, pa-liū́tė “long and heavy rain, a period of rains”. The palatalized l’< *li̯ of liū́tis, pa-liū́tis and pa-liū́tė attaches to the vocalism e form * leh3u ->* leu(k)-> *liau(k)-. With respect to their prefixal derivation the lake name Lith. At-lavas and Lat. ab-luvium, dī-luvium etc. “effusion, overflow, inundation, deluge” may be also compared and their root morpheme *-loui̯o- with the lake name Lith. Laujà identified. Due to structural analogy (:* leh3-u -) there might have existed a parallel form * leh3-i- conserved in Lith. líeti (praes. líeja, lẽja, praet. líejo, lė́jo) ”pour“ and Latv. liêt (praes. leju, praet. lêju) “id.”, from which Lith. lietús “rain”, Latv. liêtus “id.” are derived with suffix -tu-.